Composite film as well as preparation method and application thereof

By preparing SrRuO3 and SrTiO3 single-crystal oxide films on ITO thin films and then performing water-soluble sacrificial layer peeling and oxygen atmosphere annealing, the problem of preparing single-crystal oxide films on ITO substrates was solved, achieving high stability and high efficiency resistive switching performance, suitable for thin film devices.

CN121038593APending Publication Date: 2025-11-28WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511163291.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing technologies make it difficult to fabricate single-crystal oxide thin films on ITO substrates, resulting in poor device stability and reliability, which limits the development of ITO-based oxide thin film devices.

Method used

SrRuO3 and SrTiO3 single-crystal oxide films were prepared on ITO films using pulsed laser deposition and ion sputtering techniques. Self-supporting composite films were formed by water-soluble sacrificial layer peeling and oxygen atmosphere annealing, which optimized the oxygen vacancy distribution and interface structure.

Benefits of technology

It achieves high stability and high efficiency resistive switching performance. The composite thin film can quickly switch resistive states under the action of an electric field, and has significant rectification characteristics and excellent resistive switching performance, making it suitable for thin film devices, especially memristors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121038593A_ABST
    Figure CN121038593A_ABST
Patent Text Reader

Abstract

The invention provides a composite film. The composite film comprises an ITO (Indium Tin Oxide) film, an SrRuO3 single crystal oxide film and an SrTiO3 single crystal oxide film, the SrRuO3 single crystal oxide thin film is arranged on the surface of the ITO thin film, an ohmic contact interface exists between the SrRuO3 single crystal oxide thin film and the ITO thin film, and the ohmic contact interface comprises a solid solution obtained by replacing Ru atoms in SrRuO3 unit cells with In atoms and a solid solution obtained by replacing In atoms in ITO with Ru atoms; the ITO thin film is arranged on the surface of the SrRuO3 single crystal oxide thin film, the SrTiO3 single crystal oxide thin film is arranged on the surface, far away from the ITO thin film, of the SrRuO3 single crystal oxide thin film, the lattice oxygen content in the SrTiO3 single crystal oxide thin film is 45-55%, and a top electrode is further arranged on the surface, far away from the SrRuO3 single crystal oxide thin film, of the SrTiO3 single crystal oxide thin film. The invention also discloses a preparation method and application of the composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thin film materials technology, specifically to a composite thin film, its preparation method, and its application. Background Technology

[0002] In recent years, with the rapid development of thin film preparation technology, functional oxide thin film materials and devices prepared on functional substrates have broad application prospects in the core microelectronics industry due to their rich functional characteristics. Among them, ITO transparent conductive thin film glass, as an important transparent conductive substrate, is widely used in the preparation and research of thin film devices and has been used in memory devices, optoelectronic devices and other fields.

[0003] Currently, the industry uses physical vapor deposition (PVD) or chemical vapor deposition (CVD) processes to deposit oxide thin films on ITO substrates. However, due to lattice mismatch, single-crystal oxide thin films are difficult to grow epitaxially on ITO. Therefore, the films deposited on the ITO surface are polycrystalline / amorphous oxide films. The presence of grain boundaries and grains in these polycrystalline / amorphous films directly leads to a decrease in the stability and reliability of the devices. Thus, the development of ITO-based oxide thin film devices is severely limited by the upper polycrystalline oxide film, and overcoming this constraint has become a focus of attention for both research and industry.

[0004] Single-crystal functional oxide thin films and devices often exhibit better stability and reliability than polycrystalline thin film devices due to their superior lattice structure and uniformity. Therefore, for ITO-based oxide thin film devices, it is urgent to find new process methods to realize the preparation and performance optimization of single-crystal oxide thin films on ITO substrates.

[0005] In 2016, Lu Di et al. of Stanford University successfully achieved the peeling and transfer of substrate-free "self-supporting" perovskite oxide film for the first time by using a water-soluble intermediate sacrificial layer method, which provided inspiration for the development of novel low-dimensional functional oxide thin film materials and device assembly. Summary of the Invention

[0006] The first objective of this invention is to provide a composite thin film with excellent resistive switching properties.

[0007] A second objective of this invention is to provide a method for preparing composite films with stable performance.

[0008] A third objective of this invention is to provide an application of the composite thin film in a thin-film device.

[0009] To achieve the above objectives, the present invention provides the following technical solution: A composite film, comprising ITO thin film, SrRuO3 single crystal oxide thin film and SrTiO3 single crystal oxide thin film; The SrRuO3 single crystal oxide film is disposed on the surface of the ITO film, and there is an ohmic contact interface between the SrRuO3 single crystal oxide film and the ITO film. The ohmic contact interface includes a solid solution obtained by replacing Ru atoms in the SrRuO3 unit cell with In atoms and a solid solution obtained by replacing In atoms in the ITO with Ru atoms. The SrTiO3 single crystal oxide film is disposed on the surface of the SrRuO3 single crystal oxide film away from the ITO film, and the lattice oxygen content in the SrTiO3 single crystal oxide film is 45-55%. The surface of the SrTiO3 single crystal oxide film away from the SrRuO3 single crystal oxide film is also provided with a top electrode.

[0010] Preferably, the thickness of the SrRuO3 single-crystal oxide film is 60-80 nm; The thickness of the SrTiO3 single crystal oxide film is 120-160 nm.

[0011] Preferably, the top electrode is an Au electrode; the thickness of the top electrode is 50nm-200nm.

[0012] The method for preparing the composite thin film includes the following steps: S1 sequentially deposits a water-soluble sacrificial layer, a SrRuO3 single-crystal oxide film, and a SrTiO3 single-crystal oxide film on the substrate surface, and then loads a top electrode on the SrTiO3 single-crystal oxide film surface. S2 removes the sacrificial layer, separating the SrRuO3 single crystal oxide film and the SrTiO3 single crystal oxide film from the substrate, and obtaining a self-supporting single crystal oxide film composed of the SrRuO3 single crystal oxide film and the SrTiO3 single crystal oxide film. S3 transfers the self-supporting single-crystal oxide film to the surface of the ITO film, wherein the top electrode is located away from the surface of the ITO film, and finally annealing is performed in an oxygen atmosphere to obtain the composite film.

[0013] Preferably, the deposition in S1 includes the steps of sequentially depositing a water-soluble sacrificial layer, a SrRuO3 single-crystal oxide film, and a SrTiO3 single-crystal oxide film on the substrate surface using a pulsed laser method; The method for loading the top electrode described in S1 includes the step of loading Au onto the surface of a SrTiO3 single-crystal oxide film using ion sputtering to form the top electrode.

[0014] Preferably, the target material used in the pulsed laser method for depositing the sacrificial layer is Sr3Al2O6; the thickness of the sacrificial layer is 30-50 nm. The target material used in the pulsed laser method for depositing SrRuO3 single crystal oxide thin films is a SrRuO3 single crystal target. The target material used in the pulsed laser method for depositing SrTiO3 single crystal oxide thin films is an SrTiO3 single crystal target. The pulsed laser method uses a KrF excimer laser; In the pulsed laser method, the distance between the target and the substrate is 4-8 cm during the deposition of the sacrificial layer; In the pulsed laser method, the distance between the target and the substrate is 4-8 cm when depositing single-crystal oxide thin films; The pulsed laser method uses a pulse frequency of 5-20Hz; The pulsed laser method uses a laser energy density of 1.5-30 J / cm². 2 , The pulsed laser method uses a deposition temperature of 600℃-800℃. The pulsed laser method used a flow oxygen pressure of 15 Pa when depositing SrRuO3 single-crystal oxide thin films. The pulsed laser method used to deposit SrTiO3 single-crystal oxide thin films employs a flowing oxygen pressure of 5 × 10⁻⁶. -3 Pa.

[0015] Preferably, the mask used in the ion sputtering method is a gold electrode array mask; The diameter of a single electrode in the top electrode is 50-200 micrometers; The spacing between individual electrodes in the top electrode is 100-500 micrometers; The gas flow rate used in the ion sputtering method is 5-20 sccm; The ion sputtering method uses a sputtering power of 80-150W.

[0016] Preferably, step S3 includes the steps of transferring the self-supporting single-crystal oxide film to the surface of the ITO film using a support layer, and then removing the support layer; The support layer is polydimethylsiloxane.

[0017] Preferably, the annealing in S3 is performed using a pulsed laser deposition apparatus; the heating and cooling are achieved using a platinum wire heating plate within the cavity of the pulsed laser deposition apparatus.

[0018] The annealing described in S3 uses an oxygen atmosphere; The oxygen pressure used for annealing described in S3 is 100-150 Pa; The annealing temperature described in S3 is 400-600℃; The annealing heating rate described in S3 is 5-10℃ / min; The holding time for annealing described in S3 is 20-30 minutes; The annealing cooling rate described in S3 is 3-5℃ / min.

[0019] The composite film described above is used in the fabrication of thin-film devices.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a composite thin film with resistive switching effect, wherein an SrTiO3 single-crystal thin film is used to provide oxygen vacancies (since oxygen vacancy concentration is difficult to characterize, and lattice oxygen content is related to oxygen vacancy concentration, this invention uses lattice oxygen concentration to characterize oxygen vacancy concentration), so that the composite thin film exhibits resistive switching effect. It is known that oxygen vacancies in the SrTiO3 single-crystal thin film can diffuse into the SrRuO3 single-crystal thin film, while oxygen vacancies in the SrRuO3 single-crystal thin film are difficult to diffuse into the SrTiO3 single-crystal thin film. After applying a negative bias voltage to the composite thin film, positively charged oxygen vacancies in both the SrTiO3 and SrRuO3 single-crystal thin films migrate along the direction of the electric field, forming a concentration gradient of oxygen vacancies from high to low. Simultaneously, because oxygen vacancies in the SrRuO3 single-crystal film are difficult to diffuse into the SrTiO3 single-crystal film, oxygen vacancies accumulate at the interface between the SrRuO3 and SrTiO3 single-crystal films, forming an interface oxygen vacancy defect accumulation layer. This reduces the resistance at the interface between the SrRuO3 and SrTiO3 single-crystal films (the higher the oxygen vacancy concentration, the lower the resistance). At this point, the composite film is in a low-resistivity state. When a positive bias is applied to the composite film, due to oxygen vacancy migration, a concentration gradient of oxygen vacancies forms along the direction of the positive bias electric field. Since oxygen vacancies tend to move away from the interface between the SrTiO3 and SrRuO3 single-crystal films, an interface oxygen vacancy defect depletion layer forms at the interface between the SrRuO3 and SrTiO3 single-crystal films, increasing the resistance. At this point, the composite film is in a high-resistivity state. Due to the difference in work function and the presence of the aforementioned oxygen vacancy concentration gradient, a Schottky interface is formed at the contact surface between the SrTiO3 and SrRuO3 single-crystal films, exhibiting rectification characteristics in the IV curve. However, for the composite film to show significant hysteresis in its IV curve, oxygen vacancies in the film need to migrate to the interface and accumulate or be depleted under a positive (negative) electric field, exhibiting a differential concentration gradient distribution. Therefore, the oxygen vacancy concentration in the SrTiO3 single-crystal film cannot be too high or too low. When the lattice oxygen concentration in the SrTiO3 single-crystal film is 45-55%, the corresponding oxygen vacancy concentration is just right to make the composite film's IV curve show significant hysteresis, resulting in a high (low) resistive switching effect in the composite film under a positive (negative) electric field. Simultaneously, the interdiffusion of In and Ru elements at the interface between the SrRuO3 single-crystal film and the ITO film results in a substitutional solid solution structure in both films. This structure transforms the van der Waals interface between the SrRuO3 and ITO films into a barrier-free ohmic contact interface. Therefore, SrRuO3 and ITO together serve as the bottom electrode. The unidirectional diffusion of oxygen vacancies at the Schottky interface of the SrTiO3 / SrTiO3 film allows the film to maintain its original high (low) resistance state for a long time.Therefore, the composite film provided by the present invention is a composite film with strong overall resistive switching performance and high stability.

[0021] Compared to polycrystalline oxide thin films, the single-crystal thin film in the composite thin film provided by this invention has a regular and orderly internal atomic arrangement and fewer defects, which makes the rectification characteristics and resistance state more stable during long-term use, and the performance fluctuation caused by changes in its internal structure is also smaller.

[0022] The preparation method provided by this invention utilizes a wet etching process to etch an intermediate sacrificial layer, thereby obtaining substrate-free, self-supporting single-crystal oxide films (i.e., SrRuO3 single-crystal films and SrRuO3 single-crystal films). These films are then transferred to the surface of conductive ITO glass, and a composite film is successfully prepared through an oxygen atmosphere annealing process. In this preparation method, the transfer of the single-crystal oxide films is carried out under ambient temperature and pressure conditions, overcoming the traditional high-temperature and high-pressure preparation environment and reducing the difficulty of preparing the composite film.

[0023] The preparation method provided by this invention utilizes an oxygen atmosphere annealing process to effectively optimize the high-quality single-crystal structure of the self-supporting single-crystal oxide film and regulate the oxygen vacancy defects in SrTiO3. At the same time, it enables oxygen vacancies to diffuse unidirectionally into SrRuO3, thereby changing the band structure and semiconductor properties of SrTiO3 and SrRuO3, further modulating the interface barrier of the composite film, and making the composite film exhibit significant resistive switching performance.

[0024] The composite thin film provided by this invention has high charge transport efficiency, enabling it to rapidly transition to a resistive state when a voltage is applied. Therefore, the resistive-to-variable switching ratio is significantly improved, reaching 10. 4 Furthermore, it can switch quickly and sensitively between high and low resistance states, and can maintain the original high (low) resistance state for up to 10 seconds. 5 Seconds. It is evident that the resistive switching performance of the composite thin film provided by this invention is significantly superior to that of traditional ITO-based polycrystalline oxide thin films, and therefore it can be applied to the fabrication of thin-film devices, particularly thin-film memristors. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the composite thin film preparation method provided by the present invention; Figure 2 This is a schematic diagram of the structure before the self-supporting single-crystal oxide film is transferred to the surface of the ITO film in an embodiment of the present invention; wherein, 1 represents the ITO film, 2 represents the SrRuO3 single-crystal oxide film, 3 represents the SrTiO3 single-crystal oxide film, and 4 represents the top electrode. Figure 3This is a schematic diagram of the structure after the self-supporting single-crystal oxide film is transferred to the surface of the ITO film in an embodiment of the present invention; wherein, 1 represents the ITO film, 2 represents the SrRuO3 single-crystal oxide film, 3 represents the SrTiO3 single-crystal oxide film, and 4 represents the top electrode. Figure 4 This is an optical microscope image of a self-supporting single-crystal oxide thin film prepared by wet etching and stripping in an etching solution in an embodiment of the present invention. Figure 5 An optical microscope image of the composite thin film provided in an embodiment of the present invention; Figure 6 This is a transmission electron microscope cross-sectional view of the self-supporting single-crystal oxide film transferred to the ITO surface in an embodiment of the present invention; Figure 7 This is a transmission electron microscope cross-sectional view of the interface of the self-supporting single-crystal oxide thin film transferred to the ITO surface in an embodiment of the present invention; Figure 8 This is a transmission electron microscope cross-sectional view of the composite film transferred to the ITO surface in an embodiment of the present invention; Figure 9 This is a line distribution diagram of the element content of the composite film transferred to the ITO surface in an embodiment of the present invention; Figure 10 XPS energy dispersive spectroscopy and oxygen vacancy defect content analysis of the composite film before and after oxygen atmosphere annealing in the embodiments of the present invention. Figure 11 The diagram illustrates the interface barrier and oxygen vacancy defects of the composite thin film in this embodiment of the invention, forming a high-resistivity / low-resistivity state. Figure 12 The IV characteristics of the composite film in this embodiment of the invention before and after oxygen atmosphere annealing. Figure 13 This is an IV characteristic diagram of the composite film after oxygen atmosphere annealing in an embodiment of the present invention, taken at different voltage scanning ranges. Figure 14 This is an IV characteristic diagram of the composite film after oxygen atmosphere annealing in an embodiment of the present invention, which is cyclically scanned 20 times within a voltage range of ±5V. Figure 15 This is a schematic diagram of the high / low impedance state modulation switching of the composite film after oxygen atmosphere annealing in an embodiment of the present invention under ±5V pulse voltage; Figure 16 This is a schematic diagram showing the high / low resistivity retention time of the composite film after oxygen atmosphere annealing in an embodiment of the present invention. Detailed Implementation

[0026] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings. It should be noted that the description of these embodiments is for the purpose of helping to understand the present invention, but does not constitute a limitation of the present invention.

[0027] Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0028] This invention provides a method for preparing a composite thin film. Specifically, the method includes the following steps: Step 1: Using pulsed laser deposition and ion sputtering techniques with an excimer laser, a water-soluble sacrificial layer, a SrRuO3 single-crystal oxide film, and a SrTiO3 single-crystal oxide film are sequentially epitaxially deposited on a single-crystal epitaxial substrate. Then, a top electrode is loaded on the surface of the SrTiO3 single-crystal oxide film to obtain a stacked structure of single-crystal epitaxial substrate-sacrificial layer-SrRuO3 single-crystal oxide film-SrTiO3 single-crystal oxide film-top electrode. Step 2: Place the stacked structure into the etching solution to etch away the sacrificial layer, thereby separating the SrRuO3 single-crystal oxide film in the stacked structure from the single-crystal epitaxial substrate and obtaining a self-supporting single-crystal oxide film. Step 3: The self-supporting single-crystal oxide film is transferred to the surface of the ITO film using a flexible polymer support layer, wherein the top electrode is located away from the surface of the ITO film. The film is annealed in an oxygen atmosphere. By annealing in an oxygen atmosphere, the oxygen vacancy defects, conductivity and interface barrier of the self-supporting single-crystal oxide film are controlled to prepare a composite film.

[0029] In this invention, the oxygen atmosphere annealing process affects the conductivity mechanism of the composite film as follows: 1. The interdiffusion of In and Ru elements at the interface between the SrRuO3 single-crystal oxide film and the ITO film results in a substitutional solid solution structure in both films. This structure transforms the van der Waals interface between the SrRuO3 single-crystal oxide film and the ITO film into a barrier-free ohmic contact interface, thereby enabling conductivity between the self-supporting single-crystal oxide film and the ITO film, achieving the technical effect of using ITO as an electrode for the single-crystal oxide film; 2. The annealing process can optimize the SrRuO3 single-crystal oxide film and the SrTiO3 single-crystal oxide film. The structural defects of the thin film, including oxygen vacancy defects, enable the self-supporting oxide film to exhibit a high-quality single-crystal lattice structure. Furthermore, the interface defect engineering between the SrRuO3 and SrTiO3 single-crystal oxide films was optimized, resulting in a clear bilayer interface and an ordered atomic structure, thereby optimizing the interface band structure of the bilayer single-crystal film. 3. The annealing process reduced the oxygen vacancy content of the single-crystal oxide film, further optimizing its semiconductor properties. This appropriate concentration of oxygen vacancies diffuses and migrates within and at the interface of the film, exhibiting a concentration gradient distribution. This results in a significant hysteresis characteristic in the IV curve of the composite film, demonstrating remarkable resistive switching performance. Example 1

[0030] Perovskite-structured SrTiO3 was selected as the single-crystal epitaxial substrate. The single-crystal substrate was sequentially immersed in acetone, ethanol, and deionized water for ultrasonic cleaning for 10-15 minutes, dried with nitrogen, and then placed on the heating stage of the deposition chamber. Sr3Al2O6 was selected as the target material for the water-soluble sacrificial layer, and the distance between the target and the substrate was set to... , The pulse frequency of the excimer laser is 5 -20 The laser energy density is controlled at 1.5. -30 Between 600℃ and 800℃, a water-soluble sacrificial layer was epitaxially deposited. During the thin film process, the oxygen pressure is set to The target material is sputtered under the action of a laser, and the resulting atoms are deposited on the substrate surface. After 3-5 minutes of deposition, a coating with a thickness of 30 mm is obtained. -50 of thin film Substrate. Example 2

[0031] Single-crystal oxide films were deposited on the surface of the sacrificial layer film, using SrRuO3 and SrTiO3 single-crystal oxide targets sequentially. During the epitaxial deposition of the SrRuO3 single-crystal oxide film, the oxygen pressure was set to 15 Pa, and after 5-10 minutes of deposition, a SrRuO3 film with a thickness of 60-80 nm was obtained. During the epitaxial deposition of the SrTiO3 single-crystal oxide film, the oxygen pressure was set to 5 × 10⁻⁶ Pa. -3 After deposition for 15-20 minutes, a thin film with a thickness of 120-160 nm is obtained. After deposition, the stacked structure of single crystal epitaxial substrate-sacrificial layer-single crystal oxide film is obtained. Example 3

[0032] A circular gold electrode array mask was designed with an electrode diameter of 50-200 micrometers and an electrode spacing of 100-500 micrometers. Argon gas was introduced as the sputtering gas with a flow rate of 5-20 sccm and a sputtering power of 80W-150W. After sputtering the gold target for 10-30 minutes, a gold electrode with a thickness of 50nm-200nm was obtained. After sputtering, the stacked structure of the single-crystal epitaxial single-crystal oxide-top electrode was obtained.

[0033] like Figure 4 and Figure 5 A flexible polymer, polydimethylsiloxane (PDMS), was deposited as a support layer on top of a thin film stack with a gold electrode array. The sample was then etched in deionized water. The surface tension of the deionized water was used to separate the single-crystal oxide film from the single-crystal substrate, resulting in a self-supporting single-crystal oxide film-electrode structure. The self-supporting single-crystal oxide film was then transferred to the target substrate, ITO-coated conductive glass, using the flexible PDMS support layer. The flexible PDMS support layer was then removed by heating, successfully transferring the self-supporting single-crystal oxide film to the ITO-coated conductive glass, thus obtaining a composite film. The entire process is as follows: Figure 2 and Figure 3 . Example 4

[0034] The self-supporting single-crystal oxide film transferred to the ITO surface in Example 3 was subjected to oxygen atmosphere annealing. The specific steps included: placing the single-crystal oxide film transferred to the ITO surface into the cavity of a pulsed laser deposition equipment with a base vacuum of 10. -3 -10 -5 High-purity oxygen is introduced at a pressure of 100-150 Pa, and the temperature is increased to 400-600℃ at a rate of 5℃ / min-10℃ / min. After reaching the set temperature, it is held for 20-30 minutes, and then cooled to room temperature in the chamber at a rate of 3℃ / min-5℃ / min. Oxygen atmosphere annealing is then completed.

[0035] The film structure of the composite film on the ITO surface after annealing in an oxygen atmosphere in Example 4 was characterized. Figure 6 These are the results of high-resolution transmission electron microscopy (HRTEM) and diffraction patterns of self-supporting single-crystal oxide films transferred to the ITO surface after oxygen atmosphere annealing. The results confirm that the structural defects in the self-supporting single-crystal oxide films after oxygen atmosphere annealing are optimized, and the self-supporting oxide films exhibit a high-quality single-crystal lattice structure.

[0036] Figure 7 These are the results of high-resolution transmission electron microscopy (HRTEM) experiments on the interface of a self-supporting single-crystal oxide SrTiO3 / SrRuO3 film transferred to the ITO surface after oxygen atmosphere annealing. The results further confirm that oxygen atmosphere annealing has an optimizing effect on the interface defect engineering of the bilayer self-supporting single-crystal oxide SrTiO3 / SrRuO3 film, with a clear bilayer film interface and an ordered atomic structure.

[0037] Figure 8 and Figure 9 The images show a transmission electron microscope (TEM) cross-sectional view and elemental distribution map of the composite film transferred to the ITO surface after annealing in an oxygen atmosphere. The interaction force between the ITO and the upper self-supporting single-crystal oxide film is a van der Waals force. Figure 9 The interlayer element content distribution indicates that the oxygen atmosphere annealing treatment causes interlayer interdiffusion of Ru and In elements between the self-supporting single crystal SrRuO3 film and the ITO surface layer, inducing the formation of a substitution solid solution structure within the self-supporting single crystal SrRuO3 film. This structure leads to the formation of an ohmic contact interface between the SrRuO3 single crystal oxide film and the ITO interface, without an interface barrier.

[0038] XPS results of self-supporting oxide SrTiO3 films before and after oxygen atmosphere annealing are shown in [reference]. Figure 10 ,from Figure 10 It can be seen that annealing in an oxygen atmosphere leads to a significant difference in the peak position of the O element in the photoelectron spectrum of the thin film, resulting in an increase in the lattice oxygen content on the surface of the self-supporting single-crystal oxide SrTiO3 film from 14.4% to 51.1%, confirming a significant reduction in the oxygen vacancy content. Furthermore, the different chemical potentials of the SrRuO3 and SrTiO3 films cause oxygen vacancies to preferentially diffuse unidirectionally from SrTiO3 to SrRuO3. Therefore, a sharp interface, i.e., an oxygen vacancy accumulation layer or depletion layer (more than 10 unit cell thickness, 4 nm), can form near the interface of the SrRuO3 film under a bias load. Figure 11 The presence of the oxygen vacancy accumulation layer or depletion layer, as well as the difference in work function between the SrRuO3 film and the SrTiO3 film, leads to the formation of a Schottky barrier at their interface, resulting in the composite film of the present invention possessing rectification characteristics and resistive switching performance.

[0039] The effect of oxygen atmosphere annealing on the properties of composite films, such as Figure 12 It can be seen that after annealing in an oxygen atmosphere, the IV curve of the film shows obvious hysteresis, and the film exhibits resistivity switching properties, confirming that the annealing process of the present invention can lead to resistivity switching properties in the single-crystal oxide film on the ITO surface.

[0040] The resistive switching properties of the annealed composite film in Example 4 were specifically tested. The instrument used for the performance testing was a Keithley 2450 digital source meter. Different ranges of scanning bias voltage were applied to the composite film using the Keithley 2450 digital source meter, and the IV curves were measured. The test results are shown in [reference needed]. Figure 13 ,from Figure 13 As can be seen, with the increase of the scanning bias range, the composite film exhibits significant IV reverse rectification characteristics and hysteresis curves due to the presence of the interface Schottky barrier. Negative bias keeps the composite film in a low-resistance state (Set operation), while positive bias keeps it in a high-resistance state (Reset operation). A fixed range of scanning bias (0-5V--5V-0V) was applied to the composite film prepared in Example 4 using a Keithley 2450 digital source meter, and the IV curves were tested 20 times. The test results are shown in [reference needed]. Figure 14 ,from Figure 14 It can be seen that the composite film exhibits a significant IV hysteresis curve, and the high-resistivity state (HRS) and low-resistivity state (LRS) of the composite film show good cycle repeatability. Using a Keithley 2450 digital source meter, pulse voltages of ±5V and 1ms were alternately applied to the composite film prepared in Example 4 to control the switching between its high / low resistance states. The test results are as follows: Figure 15 As shown, from Figure 15 It can be seen that the resistive switching ratio of this composite thin film is greatly improved, reaching 10. 4 Furthermore, the composite film prepared in Example 4 of this invention can switch rapidly and sensitively between high and low resistance states, demonstrating its excellent rectification characteristics and resistive switching performance. Using a Keithley 2450 digital source meter, pulse voltages of +5V and -5V were applied to the composite film prepared in Example 4, triggering it to the high resistance state (HRS) and low resistance state (LRS), respectively. Its resistance state retention characteristics were tested, and the test results are as follows: Figure 16 As shown, from Figure 16 It can be seen that the composite film can maintain its original high (low) resistance state for up to 10... 5 The time interval indicates that the resistive switching performance of the ITO-based single-crystal oxide composite thin film prepared in Example 4 of this invention is stable.

[0041] The resistance switching performance of the ITO-based single-crystal oxide composite film prepared in Example 4 of the present invention was compared with that of the reported ITO-based polycrystalline / amorphous oxide films, as shown in Table 1. This confirms that the composite film provided by the present invention has better resistance switching performance than the traditional ITO polycrystalline oxide film.

[0042] Table 1

[0043] While the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the invention. Any variations and modifications can be made by those skilled in the art without departing from the spirit and scope of the invention. Therefore, any modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention, without departing from the scope of the invention, fall within the protection scope defined by the claims of the present invention.

Claims

1. A composite thin film, characterized in that: include ITO thin film, SrRuO3 single crystal oxide thin film and SrTiO3 single crystal oxide thin film; The SrRuO3 single crystal oxide film is disposed on the surface of the ITO film, and there is an ohmic contact interface between the SrRuO3 single crystal oxide film and the ITO film. The ohmic contact interface includes a solid solution obtained by replacing Ru atoms in the SrRuO3 unit cell with In atoms and a solid solution obtained by replacing In atoms in the ITO with Ru atoms. The SrTiO3 single crystal oxide film is disposed on the surface of the SrRuO3 single crystal oxide film away from the ITO film, and the lattice oxygen content in the SrTiO3 single crystal oxide film is 45-55%. The surface of the SrTiO3 single crystal oxide film away from the SrRuO3 single crystal oxide film is also provided with a top electrode.

2. The composite film as described in claim 1, characterized in that: The thickness of the SrRuO3 single crystal oxide film is 60-80 nm; The thickness of the SrTiO3 single crystal oxide film is 120-160 nm.

3. The composite film as described in claim 1, characterized in that: The top electrode is an Au electrode; the thickness of the top electrode is 50nm-200nm.

4. The method for preparing the composite thin film as described in claim 1, characterized in that, Includes the following steps: S1 sequentially deposits a water-soluble sacrificial layer, a SrRuO3 single-crystal oxide film, and a SrTiO3 single-crystal oxide film on the substrate surface, and then loads a top electrode on the SrTiO3 single-crystal oxide film surface. S2 removes the sacrificial layer, separating the SrRuO3 single crystal oxide film and the SrTiO3 single crystal oxide film from the substrate, and obtaining a self-supporting single crystal oxide film composed of the SrRuO3 single crystal oxide film, the SrTiO3 single crystal oxide film and the top electrode. S3 transfers the self-supporting single-crystal oxide film to the surface of the ITO film, wherein the top electrode is located away from the surface of the ITO film, and finally annealing is performed in an oxygen atmosphere to obtain the composite film.

5. The method for preparing the composite thin film according to claim 4, characterized in that: The deposition described in S1 includes the steps of sequentially depositing a water-soluble sacrificial layer, a SrRuO3 single-crystal oxide film, and a SrTiO3 single-crystal oxide film on the substrate surface using a pulsed laser method; The method for loading the top electrode described in S1 includes the step of loading Au onto the surface of a SrTiO3 single-crystal oxide film using ion sputtering to form the top electrode.

6. The method for preparing the composite thin film according to claim 5, characterized in that: The target material used in the pulsed laser method for depositing the sacrificial layer is Sr3Al2O6; the thickness of the sacrificial layer is 30-50 nm. The target material used in the pulsed laser method for depositing SrRuO3 single crystal oxide thin films is a SrRuO3 single crystal target. The target material used in the pulsed laser method for depositing SrTiO3 single crystal oxide thin films is an SrTiO3 single crystal target. The pulsed laser method uses a KrF excimer laser; In the pulsed laser method, the distance between the target and the substrate is 4–8 cm during the deposition of the sacrificial layer; In the pulsed laser method, the distance between the target and the substrate is 4–8 cm when depositing single-crystal oxide thin films; The pulsed laser method uses a pulse frequency of 5–20 Hz; The pulsed laser method uses a laser energy density of 1.5–30 J / cm². 2 ; The pulsed laser method uses a deposition temperature of 600℃-800℃; The pulsed laser method used a flow oxygen pressure of 15 Pa when depositing SrRuO3 single crystal oxide thin films; The pulsed laser method used to deposit SrTiO3 single-crystal oxide thin films employs a flowing oxygen pressure of 5 × 10⁻⁶. -3 Pa.

7. The method for preparing the composite thin film according to claim 5, characterized in that: The ion sputtering method uses a gold electrode array mask. The diameter of a single electrode in the top electrode is 50-200 micrometers; The spacing between individual electrodes in the top electrode is 100-500 micrometers; The gas flow rate used in the ion sputtering method is 5-20 sccm; The ion sputtering method uses a sputtering power of 80–150 W.

8. The method for preparing the composite thin film according to claim 4, characterized in that: S3 includes the steps of transferring the self-supporting single-crystal oxide film to the surface of the ITO film using a support layer, and then removing the support layer; The support layer is polydimethylsiloxane.

9. The method for preparing the composite thin film according to claim 4, characterized in that: The annealing described in S3 uses a pulsed laser deposition equipment; heating and cooling are performed using a platinum wire heating plate inside the cavity of the pulsed laser deposition equipment. The annealing described in S3 uses an oxygen atmosphere; The oxygen pressure used for annealing described in S3 is 100-150 Pa; The annealing temperature described in S3 is 400-600℃; The annealing heating rate described in S3 is 5-10℃ / min; The holding time for annealing described in S3 is 20-30 minutes; The annealing cooling rate described in S3 is 3-5℃ / min.

10. The application of the composite film as described in claim 1, characterized in that: It is used in the fabrication of thin-film devices.